Prevalence of iron deficiency anaemia among school going adolescent girls: a cross sectional study - Rahman, Afroza; Erum, Aasiy Ul; Yousuf, Amjad Waheed (International Journal of Research in Medical Sciences, 2023)
Background: The field of nutrition of women in India that has been sadly neglected pertains to the adolescent girls. The adolescent girls, the young women, the mothers to be, represent an age group which experience a crucial phase of growth. Iron deficiency anaemia is a highly prevalent and seemingly intractable problem, particularly among females of reproductive age group in developing countries. Following early childhood, during the adolescent growth spurts, the risk of iron deficiency and anaemia reappears for both boys and girls, after which it subsides for boys but remains for girls because of menstrual loss. Aim of the study was to find the prevalence of iron deficiency anaemia among school going adolescent girls in the field area of National Institute of Unani Medicine, Bangalore. Methods: The present study is an observational, cross-sectional, school health survey undertaken to know the prevalence of iron deficiency anaemia among adolescent girls in the field area of NIUM. The present study was completed within a period of 6 months from August 2008 to January 2008. Prevalence of IDA was determined on the basis of RBC indices (MCV, MCHC) and erythrocyte morphology, evaluated from the points of anisocytosis, poikilocytosis, hypochromia and microcytosis on peripheral blood smear examination. Results: In the study population (240 girls), 25% (60) subjects were affected with various grades of anaemia, i.e., 20.4% (49) were mildly anaemic and 4.6% (11) moderately anaemic. There was no case of severe anaemia. The prevalence of IDA was seen in 11.6% of study population. Conclusions: The present study provides an indication to initiate the anaemia prophylaxis measures for adolescent girls in India including nutrition education in schools. Adolescent girls should be a target group in any programme that builds demand for sustaining iron supplementation or higher dietary intake.